Check and Balance in Islam: The Role of the ‘Ulama - Abdullah, Ab Halim bin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study examines the concept of checks and balances within Islamic constitutional thought, particularly in comparison to Western constitutional doctrine. While the Western model explicitly institutionalizes separation of powers to prevent tyranny, classical Islamic jurisprudence does not articulate an equivalent formal doctrine. The research gap lies in the limited scholarly articulation of how mechanisms functionally similar to checks and balances operated within Islamic governance despite the absence of a formalized theory. This research employs a qualitative normative approach based on classical Islamic legal texts and historical practices of governance. It analyzes key principles such as the primacy of Sharī’ah, consultative governance (shūrā), and elective leadership, alongside the institutional roles of rulers and the ‘ulama. The findings reveal that although Islamic governance is often described as unitary, a form of functional separation of powers existed in practice. The ‘ulama exercised independent authority in interpreting Sharī’ah and producing fiqh, while rulers implemented administrative policies (siyāsa shar‘iyyah) within Sharī’ah boundaries. This interaction created a dynamic system of checks and balances, with legitimacy largely dependent on scholarly endorsement, thereby positioning the ‘ulama as a decisive counterbalance to political authority. However, this balance shifted due to political centralization, particularly during the late Ottoman period. This study contributes by conceptualizing an implicit model of Islamic checks and balances rooted in the dual authority of scholars and rulers, offering a novel framework to reinterpret classical Islamic governance in contemporary constitutional discourse. It also highlights the potential relevance of this model in current constitutional reform movements in Muslim-majority countries, particularly in the post-Arab Spring context.